2005
DOI: 10.1523/jneurosci.1135-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Neurogliaform Neurons Form a Novel Inhibitory Network in the Hippocampal CA1 Area

Abstract: We studied neurogliaform neurons in the stratum lacunosum moleculare of the CA1 hippocampal area. These interneurons have short stellate dendrites and an extensive axonal arbor mainly located in the stratum lacunosum moleculare. Single-cell reverse transcription-PCR showed that these neurons were GABAergic and that the majority expressed mRNA for neuropeptide Y. Most neurogliaform neurons tested were immunoreactive for ␣-actinin-2, and many stratum lacunosum moleculare interneurons coexpressed ␣-actinin-2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
351
2
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(396 citation statements)
references
References 61 publications
39
351
2
4
Order By: Relevance
“…This is consistent with previous studies pointing to the existence of a feedforward inhibitory circuit arising from direct entorhinal inputs into CA1 (Remondes and Schuman 2002). SL-INs are connected by gap junctions (Price et al 2005). Thus, activation of Island cell axons can evoke a depolarizing response broadly among SL-INs, which may propagate through gap junctions and amplify the effect of Island cell inputs to suppress MECIII input to CA1 distal dendrites.…”
Section: The Hippocampal Ca1 Area Supports Temporal Associative Learningsupporting
confidence: 92%
“…This is consistent with previous studies pointing to the existence of a feedforward inhibitory circuit arising from direct entorhinal inputs into CA1 (Remondes and Schuman 2002). SL-INs are connected by gap junctions (Price et al 2005). Thus, activation of Island cell axons can evoke a depolarizing response broadly among SL-INs, which may propagate through gap junctions and amplify the effect of Island cell inputs to suppress MECIII input to CA1 distal dendrites.…”
Section: The Hippocampal Ca1 Area Supports Temporal Associative Learningsupporting
confidence: 92%
“…aform cells (Price et al, 2005) and were found in high numbers in the hilus and subgranular zone of the dentate gyrus and CA1 stratum pyramidale and stratum oriens (Fig. 6A, Table 2), as previously reported (Freund and Buzsaki, 1996).…”
Section: ␤Ar Expression In Neuropeptide Y-positive Interneuronssupporting
confidence: 87%
“…Another type of basket cells, containing CCK, also form perisomatic contacts onto pyramidal cells; however, they are distinguished from the PV þ variety by their slower, accommodating firing patterns (Hefft and Jonas, 2005) that integrate neuromodulatory information with faster network activity (Freund, 2003;Varga et al, 2009). Interconnected networks of NPY þ neurogliaform cells mediate regional tonic inhibition through extrasynaptic volume transmission in multiple cortical and subcortical regions (Manko et al, 2012;Olah et al, 2009;Price et al, 2005). Martinotti cells, containing CR, CB, SST, NPY, and/or CCK, span both cortical lamina and cortical columns and synapse onto pyramidal cell tuft dendrites in layer I (Markram et al, 2004).…”
Section: Development Of the Gabaergic Systemmentioning
confidence: 99%